Hate Crimes in America. - Abramovitz, Melissa (Minneapolis, MN : ABDO Publishing, 2016)
Hate Crimes in America covers the history of crimes motivated by prejudice, examples of such incidents in the headlines today, and the ways in which communities are responding to these vicious acts. Aligned to Common Core Standards and correlated to state standards. Essential Library is an imprint of Abdo Publishing, a division of ABDO.
The Charleston massacre -- What are hate crimes? -- Why do hate crimes occur? -- The history of hate crimes in America -- The evolution of hate crime laws -- The nature of modern hate crime laws -- Are hate crime laws necessary? -- Free speech and hate speech -- Combating hate crimes.
Print version record.
Added to collection customer.56279.3
Keywords: Hate crimes -- Law and legislation -- United States; Hate crimes-Law and legislation-United States-Juvenile literature; Hate crimes-United States-Juvenile literature; SOCIAL SCIENCE / Criminology; Electronic books